Residential turnover and crime—Evidence from administrative data for England and Wales - Braakmann, Nils (The British journal of criminology, 2023)
This article combines administrative data on housing transactions with monthly crime data for the years 2014-18 to investigate the link between residential turnover and crime. Using a panel of 34,753 small neighbourhoods in England and Wales as well as street-level data for London, estimates from models with multiple fixed effects suggest that higher turnover is associated with higher overall crime rates. These effects are small and driven by increases in property and violent crime. Using information on price growth, I document differential effects for high-turnover, high price growth (‘attractive’) and high turnover, low price growth (‘declining’) areas.